Henoch- Schönlein Purpura Associated with Major Complications - Islam, Mohammad Zahidul (Journal of Medicine, 2010)
Henoch Schönlein Purpura is a mild disease in children and usually self-limiting. Pulmonary hemorrhage is rare in prepubertal children. Our patient had rapidly progressive glomerulonephritis, pulmonary hemorrhage, nephrotic syndrome, hypertension, intermittent intussusception, and cerebral vasulitis with seizure. Combination of such severe complications in one patient over a short span of time is very rare. In our experience, we found that combination of iv methylprednisolone pulse therapy followed by oral prednisolone plus oral cyclophosphamide to be very effective. Keywords: Henoch Schönlein Purpura, vasculitis, glomerulonephritis, pulmonary hemorrhage, intussusception DOI:10.3329/jom.v11i1.4285 J Medicine 2010: 11: 99-101